(untitled) (International Journal of Physiology, 2021)
Psychological parameters play a key role in the daily life of young adults.It was reported that there was a high incidence of suicidal rate in these age groups when compared with others. The present study was undertaken to observe the selected psychological parameters that are depression, anxiety, and stress in young adults. A total of 50 (males =25, females =25) young adults studying undergraduate allied health courses both males and females were part of the study after obtaining the written informed consent. The following criterion was used to recruit the participants. Depression, anxiety, and stress levels were assessed using the DASS-42 questionnaire. Depression scores were significantly higher in females when compared with males. Anxiety and stress scores were not significantly different among males and females. Females were in severe depression where males were moderate. Anxiety scores of males and females were mild. Stress scores of males and females were severe. The study results support earlier studies and emphasize the need to assess psychological parameters in young adults. The study also recommends detailed studies in this area.